Bank Concentration and Monetary Policy Pass-Through - Isabel Gödl-Hanisch (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper analyzes the implications of the gradual rise in bank concentration since the 1990s for the transmission of monetary policy. I use branch-level data on deposit and loan rates to evaluate the monetary policy pass-through conditional on the level of local bank concentration and bank capitalization. I find that banks operating in high-concentration markets and under-capitalized banks adjust short-term lending rates more. I then build a theoretical model with heterogeneous banks that rationalizes the empirical findings and explains the underlying mechanism. In the model, monopolistic competition in local deposit and loan markets, along with bank capital requirements, lead to frictions on the pass-through to the real economy. Counterfactual analyses highlight that the rise in bank concentration alters monetary policy pass-through by two channels: the market power and capital allocation channels. Both channels further strengthen monetary policy transmission to output and investment, amplify the credit cycle, and flatten the Phillips curve.
Keywords: E44; E51; E52; G21; 330; monetary transmission; bank heterogeneity; monopolistic competition; bank regulation